Analisis Diglosia pada Tuturan Siswa Madrasah Aliyah Al-Falah Kecamatan Lenteng - Ira Datul Aini; Qurrotu A’yun; Anggi Wijayanto; Muhammad Farhan Ramadani (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study uses a descriptive qualitative approach to analyze the forms of diglossia that occur in Indonesian language speech at Madrasah Aliyah Al-Falah. This descriptive qualitative approach provides a view or picture of the description made to understand the phenomenon or problem in depth. The purpose of this study is to obtain the results of observations and observations regarding speech that refers to the diglossia of MA Al-Falah students through conversations with prepared data codes so that they can produce data input into written language. Through this study, the author hopes to provide new insights into the diglossia of MA Al-Falah students in High and Low speech.